HOW DO PEOPLE WITH CHRONIC CONDITIONS EXPERIENCE CARE IN THE HYWEL DDA HEALTH BOARD AREA? FINDINGS FROM INTERVIEWS WITH PATIENTS. Issue 5 (18th April 2015) - Evans, B A; Morrison-Rees, S; Harris-Mayes, R; Hurlin, C
Abstract : Background: The Welsh Government's strategy to improve Chronic Conditions Management includes improving care coordination and patient self-management to reduce unscheduled care use. Welsh health boards have responsibility for implementing the strategy since 2008. In 2011, integrated working between health and social care professionals was piloted in Carmarthenshire, part of Hywel Dda Health Board. Objective: To describe how people with chronic conditions experience care in Hywel Dda Health Board including changes due to integrated working by professionals. Method: We conducted semi-structured telephone interviews with chronic conditions patients with multiple and complex conditions. Interviews were recorded, transcribed and analysed using a framework approach. The research team comprised two academic members, two service users and one manager of local health services. Results: Thirty interviews were undertaken. Experience of care had a big effect on quality of life and helped ability to self-manage, alongside personal outlook, support and information. When missing, patients struggled to manage medication and symptoms. Patients reported variation in coordination between conditions. Respondents with stable or few conditions did not generally identify gaps between different services providing their care. Patients with very poor health appeared to have well integrated care. People with multiple conditions identified lack of communication, slow information exchange and a condition-specific not person-focused approach to care. Difficulties travelling to hospital caused worry and patients missed appointments. It was difficult to discern differences in how care was delivered between Carmarthenshire and other parts of Hywel Dda Health Board. Conclusion: People with multiple and complex chronic conditions appear confident about self managing their health. Integrated working across providers seems to work best for patients who are least or most ill; otherwise people with multiple conditions complain that care is disease-specific not patient-focused. Accessing treatment should be considered as a component of care because difficult travel arrangements are preventing people attending appointments.